Morphologic and histological differentiation of gubernaculum in female fetus: a cadaveric study - Shrivastava, T.; Pandit, S.; Kumar, S. (International Journal of Research in Medical Sciences, 2017)
Background: In both male and female fetuses inguinal canal development entails a complex sequence of anatomic events involving the gubernaculum and processus vaginalis. Much has been written about the embryological development of the genital system, particularly the male genital system and the descent of the testes from the abdominal cavity into the scrotum. In this process, the gubernaculum plays a relevant although still unclear role. Despite all the studies that have been performed, controversy still exists in this anatomical region. Methods: Twenty round ligaments of uterus were dissected from female fetuses and microscopic structure was studied under light microscope using haematoxylin and eosin stain. The specimens were collected from female fetuses (8wks-26wks). One male fetus was also dissected. Results: Gubernaculum plays a crucial role in the development of the inguinal region. The gubernaculum is directly associated with the migration of the testis through the inguinal canal and probably to the scrotum; but the inguinal canal is present before testicular descent and females have both an inguinal canal and gubernaculum, although the ovaries do not migrate through the abdominal wall. Conclusions: In this anatomical region, and despite all the studies that have been performed, controversy still exists. This article attempts to study the morphology and histology and the differentiation of the gubernaculum with age.